2022
DOI: 10.1016/j.toxrep.2021.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Refractory vasodilatory shock secondary to metformin overdose supported with VA ECMO

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
(26 reference statements)
0
8
1
Order By: Relevance
“…One case report of severe MALA progressing to cardiac arrest despite ongoing CVVHD has been described but that patient was resuscitated per advanced life-support protocol for 25 min until the patient had return of spontaneous circulation 16. A man in his 30s and a woman in her 70s with severe MALA were unable to receive CVVHD due to unstable circulation but had VA-ECMO, received CVVHD and both survived severe MALA without any sequelae 17 18. To our knowledge, this case is the first to describe good outcome in a patient with MALA that progressed into refractory cardiac arrest and was treated with VA-ECMO, double CVVHD, mechanical ventilation and vasopressors.…”
Section: Discussionmentioning
confidence: 87%
“…One case report of severe MALA progressing to cardiac arrest despite ongoing CVVHD has been described but that patient was resuscitated per advanced life-support protocol for 25 min until the patient had return of spontaneous circulation 16. A man in his 30s and a woman in her 70s with severe MALA were unable to receive CVVHD due to unstable circulation but had VA-ECMO, received CVVHD and both survived severe MALA without any sequelae 17 18. To our knowledge, this case is the first to describe good outcome in a patient with MALA that progressed into refractory cardiac arrest and was treated with VA-ECMO, double CVVHD, mechanical ventilation and vasopressors.…”
Section: Discussionmentioning
confidence: 87%
“…Survival is reported in patients with levels as high as 678 μg/mL. [ 25 ] Not surprisingly, an observational study of 105 patients with MALA reported that a lower APACHE II score and time to dialysis (<6 h) are associated with lower 30-day mortality. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 39 ] The administration of methylene blue, an inhibitor of nitric oxide synthase, has been shown to provide transient improvements in hypotension. [ 25 27 ] In cases of refractory shock, venoarterial extracorporeal membrane oxygenation (ECMO) may be considered. [ 25 ] Indications for ECMO from the Extracorporeal Treatments in Poisoning Workgroup include lactate levels >20 mmol/L, pH ≤7.0, shock, failure of supportive care, and decreased level of consciousness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations